2022
DOI: 10.1002/hep.32740
|View full text |Cite
|
Sign up to set email alerts
|

The liver cancer immune microenvironment: Therapeutic implications for hepatocellular carcinoma

Abstract: The liver is the sixth most common site of primary cancer in humans and the fourth leading cause of cancer-related death in the world. Hepatocellular carcinoma (HCC) accounts for 90% of liver cancers. HCC is a prevalent disease with a progression that is modulated by the immune system. Half of the patients with HCC receive systemic therapies, traditionally sorafenib or lenvatinib, as a first-line therapy. In the last few years, immune-checkpoint inhibitors (ICIs) have revolutionized cancer therapy and have gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(155 citation statements)
references
References 248 publications
1
96
0
1
Order By: Relevance
“… 44–46 Previous study has determined that Anti-PD-L1, Anti- B7-1 (CD80) and B7-2 (CD86) checkpoint has been an innovative immunotherapeutic strategy. 47 , 48 In our study, we also found that expression levels of the PD-L1/2, B7-1 (CD80) and B7-2 (CD86) checkpoint molecules in the high-risk group were significantly increased compared with those in the low-risk group. This suggests that inhibition of these four immune checkpoint molecules can suppress the expression level of 7 gene signature, further inhibition of HCC progression.…”
Section: Discussionsupporting
confidence: 71%
“… 44–46 Previous study has determined that Anti-PD-L1, Anti- B7-1 (CD80) and B7-2 (CD86) checkpoint has been an innovative immunotherapeutic strategy. 47 , 48 In our study, we also found that expression levels of the PD-L1/2, B7-1 (CD80) and B7-2 (CD86) checkpoint molecules in the high-risk group were significantly increased compared with those in the low-risk group. This suggests that inhibition of these four immune checkpoint molecules can suppress the expression level of 7 gene signature, further inhibition of HCC progression.…”
Section: Discussionsupporting
confidence: 71%
“…In recent years, the clinical application of ICIs has increased the enthusiasm for HCC immunotherapy research. Studies showing that the combination of atezolizumab (anti-PD-L1) and bevacizumab (anti-VEGF) can significantly improve overall survival has made them first-line therapy for patients with advanced HCC ( Donisi et al, 2020 ; Donne and Lujambio, 2022 ; Sperandio et al, 2022 ). Besides ICI, there are other immunotherapy strategies under investigation, such as oncolytic virus immunotherapy and adoptive T cell transfer ( Foerster et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the risk score calculated by the model is expected to be a powerful complement to the clinical characteristics. Currently, the tumor immune microenvironment is a hot topic of research, and immune checkpoint inhibitors have been shown to be used for immunotherapy of tumors (Donne and Lujambio, 2022;Llovet et al, 2022). However, the prognosis of patients with hepatocellular carcinoma is hampered by the significant heterogeneity of patients and drug resistance after treatment (Cheng et al, 2020;Heinrich et al, 2021).…”
Section: Metabolic Abnormalities In Hepatocellular Carcinoma Exhibitmentioning
confidence: 99%